1985
DOI: 10.1248/bpb1978.8.1006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of idebenone (CV-2619) and its metabolites on respiratory activity and lipid peroxidation in brain mitochondria from rats and dogs.

Abstract: The effects of idebenone (CV-2619) and its metabolites on respiratory activity and lipid peroxidation in isolated brain mitochondria from rats and dogs were studied. CV-2619 was easily reduced by canine brain mitochondria in the presence of respiratory substrates. Reduced CV-2619 (2H-CV-2619) was rapidly oxidized through the cytochrome b chain, indicating that the compound functioned simply as an electron carrier of mitochondrial respiratory system. Both nicotinamide adenine dinucleotide (NADH)- and nicotinami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Idebenone inhibits the generation of lipid peroxide in rat brain homogenate (63), rat brain mitochondria (62), and dog brain mitochondria (60). We reported that idebenone suppressed lipid peroxide generation in rat brain mitochondria in the presence of NADH, FeC13, and ADP with a 50% inhibitory concentration of 80 p~ (62).…”
Section: Mechanism Of Actionmentioning
confidence: 94%
See 1 more Smart Citation
“…Idebenone inhibits the generation of lipid peroxide in rat brain homogenate (63), rat brain mitochondria (62), and dog brain mitochondria (60). We reported that idebenone suppressed lipid peroxide generation in rat brain mitochondria in the presence of NADH, FeC13, and ADP with a 50% inhibitory concentration of 80 p~ (62).…”
Section: Mechanism Of Actionmentioning
confidence: 94%
“…Therefore activating this energyAch (nmol/g) Choliiie 60 producing function of mitochondria stimulates cell function, which in turn may improve cerebral dysfunction caused by cerebrovascular disorders. In fact, idebenone improves energy metabolism and improves neurological symptoms and amnesia associated with cerebral apoplexy.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Different sets of biochemical experiments were used to demonstrate that idebenone could protect respiratory function and ameliorate energy metabolism in mitochondria [6,7]. Using mitochondrial assays, researchers also showed that idebenone was rapidly oxidised by mitochondrial complex III and was readily reduced by the ubiquinone reductase function of complex I, as well as by complex II and glyceraldehyde-3-phosphate dehydrogenase [8,9].…”
Section: Idebenone -An Improved Benzoquinonementioning
confidence: 99%
“…Parabenzoquinones such as CoQ 10 and its derivative or analog act by transferring electrons from complex I/II to complex II in the mitochondrial respiratory chain and are thus rapidly reduced [84]. Idebenone was demonstrated to reduce the harmful effects of iron and to protect the heart from iron related injuries [85,86].…”
Section: Antioxidantsmentioning
confidence: 99%